Investigating the Antimicrobial Activity of Vancomycin-Loaded Soy Protein Nanoparticles - Zare-Zardini, Hadi; Soltaninejad, Hossein; Ghorani-Azam, Adel; Forouzani-Moghaddam, Mohammad Javad; Mozafri, Sima; Akhoundi-Meybodi, Zohreh; Ferdosian, Farzad; Jabinian, Fatemeh (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Developing targeted and slow-release antibiotic delivery systems can effectively reduce drug overdose and side effects. This study aimed to investigate the antimicrobial activity of vancomycin-loaded soy protein nanoparticles (vancomycin-SPNs). For the preparation of SPNs, the desolvation method was applied in different concentrations of vancomycin and soy protein (15:5, 10:15, 6:20, 8:25, and 10:30 of vancomycin:soy protein). Scanning electron microscope (SEM), transmission electron microscopy (TEM), dynamic light scattering (DLS), and FTIR were used for nanoparticle characterization. Antibacterial activity was evaluated by the radial diffusion assay (RDA) and absorbance methods. Proper synthesis was demonstrated by characterization. The best drug loading (% entrapment efficiency = 90.2%), the fastest release rate (% release = 88.2%), and the best antibacterial activity were observed in ratio 10:30 of vancomycin:SPNs. Results showed that SPNs are a potent delivery system for antibiotic loading and slow release to control antibiotic use.